Solving the regulation puzzle of periderm development using advances in fruit skin - Wang, Yue-zhi; Dai, Mei-song; Cai, Dan-ying; Shi, Ze-bin (Frontiers in Plant Science, 2022)
Periderm protects enlarged organs of most dicots and gymnosperms as a barrier to water loss and disease invasion during their secondary growth. Its development undergoes a complex process with genetically controlled and environmental stress-induced characters. Different development of periderm makes the full and partial russet of fruit skin, which diverges in inheritance with qualitative and quantitative characters, respectively, in pear pome. In addition to its specific genetics, fruit periderm has similar development and structure as that of stem and other organs, making it an appropriate material for periderm research. Recently, progress in histochemical as well as transcriptome and proteome analyses, and quantitative trait locus (QTL) mapping have revealed the regulatory molecular mechanism in the periderm based on the identification of switch genes. In this review, we concentrate on the periderm development, propose the conservation of periderm regulation between fruit and other plant organs based on their morphological and molecular characteristics, and summarize a regulatory network with the elicitors and repressors for the tissue development. Spontaneous programmed-cell death (PCD) or environmental stress produces the original signal that triggers the development of periderm.  Spatio-temporal specific PCD produced by PyPPCD1 gene and its homologs can play a key role in the coordinated regulation of cell death related tissue development.